Arbuscular mycorrhizal fungi alter rhizosphere fungal community characteristics of Acorus calamus to improve Cr resistance - Xia, Guodong; Zhu, Sixi; Zhao, Wei; Yang, Xiuqing; Sheng, Luying; Mao, Huan (PeerJ, 2023)
To investigate changes in fungal community characteristics under different Cr(VI) concentration stresses and the advantages of adding arbuscular mycorrhizal fungi (AMF), we used high throughput sequencing to characterize the fungal communities. Cr(VI) stress reduced rhizosphere soil SOM (soil organic matter) content and AMF addition improved this stress phenomenon. There were significant differences in fungal community changes under different Cr(VI) concentrations. The fungal community characteristics changed through inhibition of fungal metabolic ability, as fungal abundance increased after AMF addition, and the fungal diversity increased under high Cr(VI) concentration. The dominant phyla were members of the Ascomycota, Basidiomycota, Mortierellomycota, and Rozellomycota. Dominant groups relevant to Cr resistance were Ascomycota and Basidiomycota fungi. Moreover, Fungal community characteristics were analyzed using high-throughput sequencing of the cytochrome c metabolic pathway, NADH dehydrogenase, and NADH: ubiquinone reductase and all these functions were enhanced after AMF addition. Therefore, Cr(VI) stress significantly affects fungal community structure, while AMF addition could increase its SOM content, and metabolic capacity, and improve fungal community tolerance to Cr stress. This study contributed to the understanding response of rhizosphere fungal community in AMF-assisted wetland phytoremediation under Cr stress.
Keywords: Cr stress; Arbuscular mycorrhizal fungi; Fungal community structure; Acorus calamus; ITS rRNA sequencing technology; Phytoremediation